Climate-Resilient Vegetation Monitoring in Malang Regency Using Multi-Temporal Remote Sensing - Fatih Al Haq An Nashr Muhsin; Brian Rahardi; Estri Laras Arumingtyas (Jurnal Penelitian Pendidikan IPA, 2026)
Malang Regency exhibits strong topographic and microclimatic contrasts between northern (>500 m) and southern (<500 m), which drive distinct vegetation–climate responses. This study uses MODIS MOD13Q1 NDVI/EVI (February 2000–December 2024), Landsat 8/9 (2013–2024), CHIRPS rainfall, and BMKG stations, processed in Google Earth Engine with cloud masking and compositing, to quantify long‑term vegetation trends and vegetation–rainfall relationships. Sen’s slope and Mann–Kendall tests indicate significant greening in both zones (p < 0.01), with EVI trends steeper than NDVI, reflecting EVI’s greater sensitivity to biomass dynamics in high‑biomass canopies. Annual EVI–rainfall relationships are stronger in the Southern Zone (R² = 0.545, p < 0.001) than in the Northern Zone (R² = 0.413, p < 0.01), indicating that agro ecosystems in the south remain highly responsive to seasonal rainfall fluctuations despite the presence of irrigation, whereas montane forests are more buffered by groundwater and soil‑water storage. ARIMA time‑series models provide baseline rainfall scenarios that suggest only a weak downward tendency within historical variability and are interpreted cautiously given the strong influence of ENSO and IOD. These findings offer a quantitative basis for climate‑informed land‑use planning that simultaneously considers climatic drivers, irrigation management, and ongoing urban expansion in Malang Regency.